The Implementation of e-Government in Local Authorities in Zambia - Bwalya, Tuesday; Mulundano, Clarence (Zambia ICT Journal, 2023)
Governments, both central and local authorities, have embraced the concept of e-Governance. This study sought to determine the extent of e-Government implementation by local authorities in Zambia by assessing the availability of websites/web portals, online services, and other e-Government systems in local authorities. The study also sought to establish the possible e-Government implementation challenges in local authorities. A quantitative research design approach and a survey strategy were adopted. In this regard, 35 local authorities out of 116 local authorities were purposively selected to take part in the study. Data was collected using a questionnaire and observation checklist. The findings show that only 5 (14.29 %) of local authorities have websites/web portals that provided mainly basic information, except for the website for the Lusaka city council which provided online services including online payment. Further, it was established that all the councils have Facebook pages where they provide information and engage the public. Furthermore, all the surveyed councils practice e-procurement using the Zambia e-Government Procurement platform for Zambia Public Procurement Authority. The majority (70%) of local authorities reported having several challenges which include inadequate funding, limited ICT infrastructure, and lack of skilled IT, intermittent power supply, and unstable internet connectivity.